2020
DOI: 10.1242/jcs.250274
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase-PEST mediates hypoxia-induced endothelial autophagy and angiogenesis via AMPK activation

Abstract: Global and endothelial loss of PTP-PEST (also known as PTPN12) is associated with impaired cardiovascular development and embryonic lethality. Although hypoxia is implicated in vascular remodelling and angiogenesis, its effect on PTP-PEST remains unexplored. Here we report that hypoxia (1% oxygen) increases protein levels and catalytic activity of PTP-PEST in primary endothelial cells. Immunoprecipitation followed by mass spectrometry revealed that α subunits of AMPK (α1 and α2, encoded by PRKAA1 and PRKAA2, r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…Whether such an increased binding results in altered enzymatic kinetics or can potentially lead to substrate trapping is an interesting future direction to investigate. Our earlier experimental studies have shown that AMPKα interacts with PTP-PEST under normoxic condition and that this interaction is impaired in hypoxia-treated cells 9 . The observations from the current simulations indicate an increased binding between AMPKα and PTP-PEST upon phosphorylation of Y64 on PTP-PEST.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Whether such an increased binding results in altered enzymatic kinetics or can potentially lead to substrate trapping is an interesting future direction to investigate. Our earlier experimental studies have shown that AMPKα interacts with PTP-PEST under normoxic condition and that this interaction is impaired in hypoxia-treated cells 9 . The observations from the current simulations indicate an increased binding between AMPKα and PTP-PEST upon phosphorylation of Y64 on PTP-PEST.…”
Section: Discussionmentioning
confidence: 90%
“…It is a heterotrimeric enzyme consisting of α, β and γ subunits, with each subunit having different isoforms (two α, two β and three γ isoforms) 11 . The AMPKα subunit that interacts with PTP-PEST contains the kinase domain (KD) as well as the autoinhibitory domain (AID) 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chandel et al. [ 58 ] confirmed that the protein tyrosine phosphatase, which contains proline-glutamate-serine-threonine as a potential major factor, is associated with inducing autophagy and angiogenesis by regulating hypoxia-activated AMPK signaling in endothelial cells.…”
Section: Reviewmentioning
confidence: 99%
“…There is increasing evidence suggesting the link between PTP inhibition and AMPK activation. Several biochemical consequences of PTP inhibition are believed to be executed via AMPK activation [149]. PTP1B is known to negatively modulate AMPK in peripheral tissues [33,150,151], and PTP1B deficiency is known to cause AMPK activation and autophagy [152].…”
Section: Ptp1b Inhibition Of Ampk Activation: Can Vanadium Compounds ...mentioning
confidence: 99%